Complete mitochondrial genome of six Cheilinusundulatus (Napoleon Wrasse): an endangeredmarine fish species from Sabah, Malaysia - Pressly Matthew; B. Mabel Manjaji Matsumoto; Kenneth Francis Rodrigues (2018)
We report here the complete mitochondrial (mt) genomes of six individuals of Cheilinus undulatus (Napoleon Wrasse), an endangered marine fish species. The six mt DNA sequences had an average size of 17,000 kb and encoded 22 tRNA, two sRNA, 13 highly conserved protein coding genes and a control region. The polymorphic variation (control region) in these six individuals suggests their potential use as a specific marker for phylogeographic conservation. Moreover, the sequence polymorphism within the control region (D-loop) suggests that this locus can be applied for phylogenetic studies.